Istoricul Parohiei Ortodoxe Române Osoi din Protopopiatul Dej - Rojneac, Vasile (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The study that we present in the following, compiled on the basis of the documents kept in the Archives of the Archdiocese of Vad, Feleac and Cluj and other specialized bibliographic sources (works or studies), highlights the history of the Osoi Romanian Orthodox Parish, within the Deanery of Dej, from the ancient times to the present day. Our scientific approach focuses on two important coordinates: 1. The history of the old wooden church dedicated to „Saints Michael and Gabriel” and the serving priests from the earliest times, until 2003 and 2. The construction of the new church dedicated to „Saint John Jacob the Hozevit”, during the pastorate of the priest Liviu-Vlad Moldovan, the one who currently pastors this parish. The new wall church will be consecrated by His Eminence auxiliary Bishop Benedict Bistriţeanul on May 7, 2023, a day of great significance for the believers of this parish.